Synthesis and physicochemical properties of macroporous cryogels (International Journal of Biology and Chemistry, 2015)
The current review reveals the analysis of recent research in the field of synthesis and characterization of cryogels. The theoretical aspects of the process of cryotropic gelation are considered. The influence of freezing temperature and concentrations of initial monomer mixture on the pore size of the material is discussed. The concept of process of cryotropic gelation is revealed. The potential need for further research in the field of cryotropic gelation is highlighted.